2006
DOI: 10.1161/01.hyp.0000196279.29758.f4
|View full text |Cite
|
Sign up to set email alerts
|

Out-of-Hemodialysis-Unit Blood Pressure Is a Superior Determinant of Left Ventricular Hypertrophy

Abstract: Abstract-Blood pressures (BPs) obtained in the dialysis unit correlate poorly with ambulatory BP and left-ventricular hypertrophy (LVH). We compared the performance of BP obtained within and outside the dialysis unit as a correlate of LVH. BP was obtained in the dialysis unit using routine and standardized methods and outside the dialysis unit using home and ambulatory BP monitoring in 140 patients (mean age, 56 years; 89 men; 129 blacks; and 59 with diabetes mellitus) on chronic hemodialysis for Ն3 months. Di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
150
1
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 169 publications
(169 citation statements)
references
References 27 publications
13
150
1
5
Order By: Relevance
“…These observations are consistent with many reports of an association between BP and LVH in HD patients (20,22,23). Although measurement of BP before starting and immediately at the end of dialysis is highly variable, dependent on fluid volume status and the hemodynamic effects of dialysis, it remains the clinical standard.…”
Section: Pre-hd Bp and Ca ϫ Po 4 : Increased Afterloadsupporting
confidence: 91%
“…These observations are consistent with many reports of an association between BP and LVH in HD patients (20,22,23). Although measurement of BP before starting and immediately at the end of dialysis is highly variable, dependent on fluid volume status and the hemodynamic effects of dialysis, it remains the clinical standard.…”
Section: Pre-hd Bp and Ca ϫ Po 4 : Increased Afterloadsupporting
confidence: 91%
“…However, it would be premature to discontinue home BP monitoring; home BP is associated with left ventricular hypertrophy (26) and mortality in hemodialysis patients (19), relationships that are yet to established for intradialytic BP recordings. Nonetheless, BP measurements obtained during dialysis appear to contain a larger amount of diagnostic information than what is apparent in predialysis and postdialysis BP measurements alone.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, we may be able to use this measurement instead of using the WAB. Agarwal et al (9) reported the significance of self-recorded home BP three times a day during 1 wk in HD patients and showed that home BP correspond to ambulatory BP and left ventricular hypertrophy in HD patients (10,11). Thus, BP should not be evaluated by one-point measurement before or after dialysis or after waking up but should be evaluated by the average of sequential monitoring during 1 wk.…”
mentioning
confidence: 99%